The Influence of Patients' Age on the Outcome of Treatment for Pancreatic Ductal Adenocarcinoma. Issue 2 (February 2020) - Malik, Abdullah K.; Lamarca, Angela; Siriwardena, Ajith Kumar; O'Reilly, Derek; Deshpande, Rahul; Satyadas, Thomas; Jamdar, Saurabh; Sheen, Aali; McNamara, Mairead; Hubner, Richard; Valle, Juan; De Liguori Carino, Nicola
Abstract : Objective: The aim of the study was to determine the impact of age on curative management and outcomes of patients with pancreatic ductal adenocarcinoma. Methods: Patients who underwent resection for pancreatic ductal adenocarcinoma at 2 units were retrospectively reviewed (between 2005 and 2017) and stratified by age (older patients ≥70 years). Regression analysis was used to explore factors impacting administration of adjuvant chemotherapy and survival. The Kaplan-Meier method was used to estimate overall survival (time from surgery to death). Statistical significance was set at P < 0.05. Results: From 2005 to 2014, 222 patients were identified (<70 years, n = 128; ≥70 years, n = 94). Elderly patients were less likely to receive adjuvant chemotherapy compared with younger patients (odds ratio, 0.57, P = 0.041). Tumor stage, margin, and year of surgery (post-2011 vs pre-2011) were not predictors for chemotherapy receipt ( P > 0.05). Frailty was the commonest reason (36.8%) to decline chemotherapy in elderly patients. In patients receiving adjuvant chemotherapy, completion rates ( P = 0.32) and overall survival (24 months vs 30 months, P = 0.50) were no different. Conclusions: Elderly patients demonstrate similar outcomes to younger yet are less likely to commence chemotherapy because of frailty. Holistic preoperative assessment may improve selection for curative treatment.